A state-of-the-art review of the recent advances of theranostic liposome hybrid nanoparticles in cancer treatment and diagnosis - Hannaneh Azimizonuzi; Arman Ghayourvahdat; Mareb Hamed Ahmed; Radhwan Abdul Kareem; Athmar Jaber Zrzor; Aseel Salah Mansoor; Zainab H. Athab; Shaylan Kalavi (Cancer Cell International)
Abstract Theranostics is a way of treating illness that blends medicine with testing. Specific characteristics should be present in the best theranostic agents for cancer: (1) the drugs should be safe and non-toxic; (2) they should be able to treat cancer selectively; and (3) they should be able to build up only in the cancerous tissue. Liposomes (LPs) are one of the most efficient drug delivery methods based on nanotechnology. Stealth LPs and commercial LPs have recently had an impact on cancer treatment. Using the valuable information from each imaging technique, along with the multimodality imaging functionality of liposomal therapeutic agents, makes them very appealing for personalized monitoring of how well therapeutic drugs are working against cancer in vivo and for predicting how well therapies will work. On the other hand, their use as nanoparticle delivery systems is currently in the research and development phase. Nanoscale delivery system innovation has made LP-nanoparticle hybrid structures very useful for combining therapeutic and imaging methods. LP-hybrid nanoparticles are better at killing cancer cells than their LP counterparts, making them excellent options for in vivo and in vitro drug delivery applications. Hybrid liposomes (HLs) could be used in the future as theranostic carriers to find and treat cancer targets. This would combine the best features of synthetic and biological drug delivery systems. Overarchingly, this article provided a comprehensive overview of the many LP types used in cancer detection, therapy, and theranostic analysis. An evaluation of the pros and cons of the many HLs types used in cancer detection and treatment has also been conducted. The study also included recent and significant research on HLs for cancer theranostic applications. We conclude by outlining the potential benefits and drawbacks of this theranostic approach to the concurrent detection and treatment of different malignancies, as well as its prospects. Graphical Abstract